Transition-Metal-Free Stereoselective and Regioselective Hydroamination of 2-Benzoylethynyl-4,5,6,7-tetrahydroindoles with Amino Acids - Sobenina, Lyubov N.; Tomilin, Denis N.; Ushakov, Igor A.; Mikhaleva, Albina I.; Trofimov, Boris A. (Synthesis, 2012)
A new family of unnatural amino acids possessing a tetrahydroindole moiety is obtained by nucleophilic addition of various amino acids to the triple bond of 2-benzoylethynyl-4,5,6,7-tetrahydroindoles. The reaction proceeds chemo-, regio- and stereospecifically in the presence of sodium hydroxide to give the Z-isomeric products in 35–72% yields.
Keywords: amino acids; 2-benzoylethynyl-4,5,6,7-tetrahydroindoles; nucleophilic addition; Z-isomers